IMPLEMENTASI PERATURAN MENTERI DALAM NEGERI NOMOR 113 TAHUN 2014 TENTANG PENGELOLAAN KEUANGAN DESA: STUDI DI DESAKANDUI KECAMATANGUNUNG TIMANG KABUPATEN BARITO UTARA - Beni Fernando (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Palangka Raya, 2016)
potential problems. Although the government has given the strengthening of the implementation of Law No. 6 Year 2014. The government has issued rules implementing namely: PP 43 of 2014 on the implementation of Law No. 6 Year 2014 about the village, PP 60 on the Village Fund Yang Sourced From State Budget, Permendagri 113 of 2014 concerning Financial Management of the Village. It is interesting to study in the village Kandui is implementation Permendagri 113 of 2014 is whether the government has met expectations or not. And whether this policy received a positive response from local governments and officials. The purpose of this study were: 1) .To describe the implementation of the Regulation of the Minister of the Interior No. 113 of 2014 concerning Financial Management of the Village in the Village of Mount Cuddle Kandui District of North Barito regency. 2). To describe the factors driving and inhibiting factors implementations Minister Regulation No. 113 of 2014 concerning Financial Management of the Village in the Village of Mount Cuddle Kandui District of North Barito regency. This type of research that is selected is a descriptive study presents qualitative data. Data collected by observation, interview, and documentation. Data Analysis Techniques using Flow Analysis Data Model (Miles and Huberman). Based on the results of field studies, it can be concluded as follows: 1) Implementation Permendagri 113 of 2014 in the village government Kandui has been running but not optimal. That is because still in the stage of deepening of the material and financial management pattern adjustment Kandui village. 2) As for the inhibiting factor is the presence of the current Secretary of the Village while still empty, but this does not interfere significantly. The driving factor is the existence of internal village Treasurer reliable. While external support is mentoring and coaching in financial management BPMDes village of North Barito regency.